Effects of Fucoidan on the Inhibition of Biofilm Formation of Salmonella enterica Subsp. enterica Serovar Typhimurium on Seafoods and Its Molecular Antibiofilm Mechanisms - Anamika Roy; Pantu Kumar Roy; Sung Rae Cho; Shin Young Park (Microorganisms)
Foodborne illnesses, particularly those caused by Salmonella enterica subsp. enterica Serovar Typhimurium, present a significant challenge to public health, especially within the seafood industry due to biofilm formation on foods. This study investigated the antibiofilm potential of fucoidan, a sulfated polysaccharide, against Salmonella enterica subsp. enterica Serovar Typhimurium biofilm on crab and shrimp surfaces. Fucoidan’s minimum inhibitory concentration (MIC) was determined to be 150 µg/mL. Sub-MIC (1/8, 1/4, 1/2, and MIC) were evaluated for their impact on inhibition of biofilm formation. Fucoidan treatment resulted in significant, dose-dependent inhibition in biofilm formation, achieving 2.61 log CFU/cm2 and 2.45 log CFU/cm2 reductions on crab and shrimp surfaces, respectively. FE-SEM analysis confirmed biofilm disruption and cell membrane damage. Real-time PCR showed the downregulation of quorum-sensing (luxS) and virulence (rpoS, avrA, and hilA) genes. These results propose that fucoidan has the ability as a natural antibacterial agent for controlling Salmonella enterica subsp. enterica Serovar Typhimurium biofilms in seafood processing, thereby enhancing food safety and minimizing contamination.